2015
DOI: 10.18865/ed.25.3.295
|View full text |Cite
|
Sign up to set email alerts
|

Racial Composition Over the Lifecourse: Examining Separate and Unequal Environments and the Risk for Heart Disease for African American Men

Abstract: Racial composition oveR the life couRse: examining sepaRate and unequal enviRonments and the Risk foR heaRt disease foR afRican ameRican men IntroductIonThe experiences of many African American (AA) men are associated with several health risk factors, poverty, distrust of institutions, discrimination, and isolation, which place them at greater risk for health problems. 1,2 AA men are plagued with health issues earlier in life, disproportionately suffer from preventable conditions, and suffer disproportionately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…A range of studies that draws on life-course theory has demonstrated both independent and combined influences of early (childhood) and late (adult) socioeconomic status on a variety of health outcomes (11, 28, 54). Given the potential importance of socioeconomic disadvantage in explaining health disadvantages among black men and women, it is somewhat surprising that more studies have not drawn on life-course theory to explain racial disparities in health (28, 75). In fact, a PubMed search for the terms “black,” “life course,” and “socioeconomic” produced only 26 studies.…”
Section: Framework For Studying Black Men’s Healthmentioning
confidence: 99%
“…A range of studies that draws on life-course theory has demonstrated both independent and combined influences of early (childhood) and late (adult) socioeconomic status on a variety of health outcomes (11, 28, 54). Given the potential importance of socioeconomic disadvantage in explaining health disadvantages among black men and women, it is somewhat surprising that more studies have not drawn on life-course theory to explain racial disparities in health (28, 75). In fact, a PubMed search for the terms “black,” “life course,” and “socioeconomic” produced only 26 studies.…”
Section: Framework For Studying Black Men’s Healthmentioning
confidence: 99%
“…Cardiovascular disease (CVD) becomes the leading cause of death for black males in their 40s. [13][14][15] The stress and psychological costs of trying to escape social discrimination may increase the likelihood of CVD and other deleterious health outcomes that contribute to black men's risk of an early death 16 -a classic determinant of John Henryism. 17 John Henryism suggests that black men experience chronic stressors shaped by poverty and discrimination.…”
Section: An Unmet Challenge To Public Health: Addressing Root Causes mentioning
confidence: 99%
“…[5-7] In addition, due to political and economic macrosocial policies, Black men are more likely than others to live in highly segregated and high poverty neighborhoods. [7-9]…”
Section: Introductionmentioning
confidence: 99%
“…Thus, experiences during early childhood and adult exposures together lead to poor health outcomes, which become more evident with age. [6, 9] Furthermore, past studies have generally included samples of the general population, and have not honed in on those with uncontrolled blood pressure, who are most at risk for adverse blood pressure-related outcomes. Among Blacks, within-race diversity such as nativity is rarely acknowledged, despite an urban population which is over one quarter foreign-born.…”
Section: Introductionmentioning
confidence: 99%